Deserts and semideserts - Allaby, Michael. frey50; Anderson, Robert 1966-; Crofton, Ian (Austin, TX : Raintree Steck-Vaughn, 2002)
A comprehensive look at the desert and semidesert biomes, examining their climate, plants, animals, people, and future, plus detailed views of some famous or important desert locations.
Biomes of the world -- Tropical forests of the world -- Sonoran desert -- Desert climate -- Atacama -- Desert plants Kalahari and Namib -- Desert animals -- Sahara -- People and the desert -- Gobi and Takla Makan -- Future for deserts -- Glossary -- Further research -- Index.
Keywords: Desert ecology; Desert ecology -- Maps; Desert ecology; Ecology